'If Only I Could Have Said, If Only Somebody Was Listening': Mothers' Experiences of Placing Their Child into Care. Issue 3 (27th March 2021) - Siverns, Kate; Morgan, Gareth
Abstract: Birthparents remain the most neglected focus of the adoptive triad in terms of practice, research and policy. Previous research has highlighted how the needs of parents who have their children removed are often unmet by services. This research explored the experiences of mothers, with trauma histories, who had made or agreed with the decision for their child to be placed into care. Three British mothers of children in care each participated in two semi-structured interviews. Data was analyzed using Interpretative Phenomenological Analysis. Three superordinate themes were generated: A fractured sense of motherhood highlighted the struggle with mothering identities in line with feelings of disconnection and separation; 'I wish I could turn back the clocks': Living with feelings of failure and shame illuminated the underlying feelings of guilt and shame associated with perceived failings; 'Less than a person': Becoming nothing and no-one alluded to experiences of disempowerment and dehumanization. Implications for reducing burden on adoption services are discussed through interventions sensitive to the operation of power, whilst the need for therapeutic services that acknowledge loss and grief are highlighted for relinquishing birthmothers.